If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -4) + 3x = 12 Reorder the terms: 2(-4 + x) + 3x = 12 (-4 * 2 + x * 2) + 3x = 12 (-8 + 2x) + 3x = 12 Combine like terms: 2x + 3x = 5x -8 + 5x = 12 Solving -8 + 5x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 5x = 12 + 8 Combine like terms: -8 + 8 = 0 0 + 5x = 12 + 8 5x = 12 + 8 Combine like terms: 12 + 8 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| 7x-(2x-4)=19 | | 7(4x+6)=-6(1-6x) | | 12.5y=225 | | 6(5p+8)=4(4+8p) | | x^2+13+42= | | 13+8x=x+6 | | 3x^2+30x=72 | | 15x^5-2x^3=24 | | 7x+1=-11+4x | | -x=0.75 | | B(t)=10et | | 11+8x=10x-3 | | -3(1+4p)=69 | | 3x(a-2b)+3b= | | -124=-2p+4(2-5p) | | 8a+3=6a+2 | | -124=2p+4(2-5p) | | 20=5b+8-b | | 2b+7b=9 | | 7u+49=-5u+25 | | X^2y-3xy^2-6x^2y= | | x+2/5+x=2/3 | | 8x-4+3x=8x+14 | | a^2+2a-1=0 | | 11=-13y+3y | | -3y+4+6y= | | 6m+x=24 | | 2m-3=6m-4 | | 8(n-1)=-32 | | X-15=36 | | 2(x+8)=34 | | 3m-3=6m-4 |